Sukitako enterprise : takoyaki and beverages / Muhammad Hidir Mohd Yusoff ...[et al.] - Mohd Yusoff, Muhammad Hidir; Ahmadi, Nur Athira; Ramizan, Nurul Najieha; Ruzlan, Rizq Rezza; Bahari, Siti Aminah (2022)
Business is a buying and selling activity between sellers and buyers who provide products or services. Business is one of the activities that can generate income in addition to working to improve the quality of life in a better direction. Successful businesses can generate unlimited income based on sales revenue. SukiTako Enterprise is a business that provides various types of takoyaki, which are snacks that originate from Japan. The business is conducted in retail at the Aeon Tebrau City Center kiosk, Johor Bharu. The takoyaki menu we prepare consists of flavours of shrimp, crab, chicken, and octopus. The business also provides beverages to customers such as Coca- Cola and A&W root beer. Through the provision of products like this, we are very confident that it can attract customers to buy because the Johor Bharu area is a strategic area for business activities due to its high population as a target market. The concept of a successful business will always emphasize the direction and careful planning to develop the business. Through the preparation of a business plan, every member in the business can know the whole process and direction of the business in the future. This is important because the business plan refines various things in the business such as the introduction to the business, the purpose and objectives of establishing a business, and the background of the business. With all the information in the business plan, it can give a clear picture to the individuals under the business organization in performing their duties and responsibilities in ensuring that business goals can be achieved.